Humour in the Alan Ford comic observed through the conceptual metaphor lense - Đuliman, Selma (Univerzitetska Misao, 2017)
Humour has been an inexhaustible subject of many a linguistic research effort, starting from sociolinguistics, through discourse analysis, to pragmatics. Incongruity is at the very core of all linguistic research of humour, and it entails an opposition of semantic notions, causing an imbalance between the punchline and the expectations of the cognitive agents. That is how humour is generated. The aim of this paper is to observe the way in which conceptual metaphor contributes the rise of humour in Alan Ford, a comic widely popular even today in the former Yugoslav area. The comic's popularity has been huge to the extent that many expressions and quotes have become part of everyday speech of many people.